IMAGE PROCESSING OF TEMPERATURE FIELDS FROM INFRARED TERMOGRAPHY OF MICRO-MIXERSWITH POLYMERIC SUBSTRATES - Costa Jr., J. M.; Naveira-Cotta, C. P.; Fudym, O. (Revista de Engenharia Térmica, 2014)
The present work deals with the image processing and thermal analysis of micro-mixers from the data provided by an infrared camera thermography system. The micro-mixers are prepared by photolitography on a polymeric substrate and the camera employed is the FLIR SC645 with the proprietary software ThermaCam Researcher Pro v2.10. The thermal analysis is aimed at understanding the direct contact heat transfer between two fluid streams and the polymeric substrate at different inlet temperatures and mass flow rates, within mixers of various geometric configurations. Infrared thermography is thus employed to measure the external wall temperatures fields along the mixer length. Water at different inlet temperatures has been used as the working fluid in all cases and the mass flow rates of the two streams have been imposed through independent syringe pumps. The image processing and analysis of the experimental results show the basic qualitative and quantitative features of the heat transfer phenomena and indicates that a conjugated heat transfer formulation of the micro-mixer structure should be pursued for accurate quantitative analysis in theoretical predictions.